Optimization of a self-supported cobalt oxide-based catalyst pellets for methane cracking - Toh, Brandon Teng Cong (Nanyang Technological University, 2020)
The world is at risk due to climate change hitting harder and sooner. By using hydrogen as an alternative energy source, climate change can be reduced due to the decrease in release of greenhouse gases. As such, cracking of methane has been gaining attention due to the demand of carbon oxide free hydrogen. There is high value added in the reaction due to the production of useful carbon which makes it more economic. The pyrolysis reaction can be enhanced by using a catalyst. Cobalt based catalysts have been proved that it is more stable and have more active sites. In this project, cobalt based catalysts doped with other metals of different ratios are fabricated and optimized. Their phase and stability were determined by X-ray diffraction at room temperature. Their catalytic properties at different dwelling time under methane atmosphere and effects of sintering temperature is investigated and analysed. It was found that cobalt doped with chromium catalysts are more stable chemically than cobalt doped with nickel, iron and molybdenum catalysts. They have different catalytic properties under different dwelling time. Furthermore, the sintering temperature have much effect on the strength of the catalyst.